The effects of feeder adjustment on growth performance of finishing pigs - Myers, A.J.; Bergstrom, J.R.; Goodband, Robert D.; Tokach, Michael D.; DeRouchey, Joel M.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 234 growing pigs (PIC TR4 × 1050, initially 91.4 lb) were used in an 89-d trial to determine the effects of feeder adjustment on finishing pig performance. Pigs were randomly allotted to 1 of 3 treatments. The treatments consisted of a narrow feeder adjustment (minimum gap opening of 0.50 in.), medium feeder adjustment (minimum gap opening of 0.75 in.), and wide adjustment (minimum feeder gap opening of 1.00 in.). The feeders were adjusted to the minimum gap setting, but the agitation plate could be moved upward to a maximum gap opening of 0.75, 1.00, or 1.25 in., respectively. Treatments were arranged in a completely randomized design with 9 replications of 8 pigs per pen and 1 replicate with 6 pigs. To ensure equal floor space, pen gating was adjusted to provide 8 ft2 /pig during the study. All pens had the same feeder with 2, 14-in.-wide by 4.5-in.-deep feeder holes. Pigs had ad libitum access to feed and water. All pigs were fed a corn-soybean meal-based diet containing 20% dried distillers grains with solubles (DDGS) in 4 phases. Pen weights and feed disappearance were measured every 2 wk. Also, pictures of feeders were taken and scored by a panel to detemine percentage pan coverage. Results showed that narrow, medium, and wide feeder adjustments averaged approximately 28, 58, and 75% pan coverage, respectively. From d 0 to 28, pigs exposed to increasing feeder gap had improved (linear; P ≤ 0.05) ADFI, with the greatest ADFI observed at 1.00 in. However, from d 28 to 56 and 56 to 89, ADG was not different among pigs fed from different feeder openings, and F/G was best for those fed from the 0.50-in. opening. Overall (d 0 to 89), there was a trend (P = 0.08) for increased ADG with increasing feeder opening. However, pigs fed with a 0.50-in. feeder gap had improved (linear; P < 0.03) F/G compared to those with a 0.75- or 1.00-in. feeder opening. These results suggest that from 90 to 150 lb, maximum ADG was observed with a feeder setting of 0.75 in (approximately 58% pan coverage). However, pigs fed from 150 to 270 lb had greater ADG and the best F/G at a setting of 0.50 in (approximately 28% pan coverage). Thus, it appears that optimum feeder-gap setting may differ with growth phase.
Keywords: Swine; Feeder adjustment; Feeder gap opening; Finishing pig